A novel model to implement ERP based on dynamic capabilities. Issue 7 (7th September 2015) - Chang, Tsung-Sheng; Fu, Hsin-Pin; Ku, Cheng-Yuan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose an implementation model for enterprise resource planning (ERP) based on resource-based view, and using the dynamic capability theory as its theoretical foundation. This model includes: the establishment of the objectives of the implementation, an assessment of the available resources and the scope of the implementation, the redesign/integration and organizational learning during the process, the implementation of the system, and the measurement and evaluation of its performance. Design/methodology/approach – An integrated circuits design company in Taiwan was used in a case study to examine the validity of the proposed model. Findings – When the proposed ERP implementation model was applied in this study, the results show that organizational coordination, system-process redesign and integration, and organizational learning are the critical strategies for enterprises, in order to reduce the risks during the implementation of ERP projects. Practical implications – This model can help enterprises recognize the resources needed when implementing an ERP. In addition, they need to consider the reliability of these resources, as this will increase the efficiency of the implementation, and thus the probability of success. Originality/value – Studies of past models in the implementation of ERP have been conducted in various industries. There is a need for further studies that evaluate the different concepts in terms of the effectiveness of specific methods, in order to enhance the probability of successfully implementing a dynamic system. This paper is one of the first to explain how an enterprise can implement an ERP that is based on the theory of dynamic capabilities. The case study illustrates the important, critical success factors.